IIUM Islamic Transformation Center (IIUMITC): pomoting activities based on Islamic principles under one roof - Ahmad Dahlan, Abdul Rahman; Omar, Norhazlina; Abdul Kahar, Nor Hajaratul Aswad; Haji, Aminah (Research Publish Journals, 2015)
The purpose of this paper is to promote activities based on Islamic principles under one roof. The three areas to be included in this proposal are finance, food and education. These three areas will be implemented according to Islamic guidance and placed in International Islamic University Malaysia (IIUM). In the financial part, society will be provided with the services that is safe from riba’, gharar and maisir (usury, uncertainty and gambling). Then, for food part, the society will be exposed to the important and correct methods to take healthy and halal food. Lastly, for education, the people will be prepared a library that focused on Islamic knowledge. Besides that, the center also hires experts to in Islamic knowledge to help the society. This kind of center is built to ensure the society is living based on Islamic way of life and getting the true happiness, Rahmatan lil A’lamin.